Vanity affairs: two collectors of Cypriot and Aegean antiquities examined. (11th April 2017) - Bombardieri, Luca
Abstract: This article discusses the concept of vanity and its driving role in the formation of collections of antiquities. It focuses on the parallel cases of Luigi Palma di Cesnola and Paolo Azzati and their respective collections of Aegean and Cypriot antiquities. It is argued that both the collectors were condemned by their insatiability and dissatisfaction to make analogous choices, however different they may have been in social status and in the context in which their collections were formed. These aspects influenced the way in which they were able to collect materials – but not the final result at which they aimed, which was, narcissistically, the collection itself.